2008
DOI: 10.4049/jimmunol.181.10.6738
|View full text |Cite
|
Sign up to set email alerts
|

The Common γ-Chain Cytokines IL-2, IL-7, IL-15, and IL-21 Induce the Expression of Programmed Death-1 and Its Ligands

Abstract: The programmed death (PD)-1 molecule and its ligands (PD-L1 and PD-L2), negative regulatory members of the B7 family, play an important role in peripheral tolerance. Previous studies have demonstrated that PD-1 is up-regulated on T cells following TCR-mediated activation; however, little is known regarding PD-1 and Ag-independent, cytokine-induced T cell activation. The common gamma-chain (gamma c) cytokines IL-2, IL-7, IL-15, and IL-21, which play an important role in peripheral T cell expansion and survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
345
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(379 citation statements)
references
References 53 publications
23
345
1
10
Order By: Relevance
“…These studies did not examine Tim-3 or PD-1 expression on T cells. The gc cytokines IL-2, IL-7, IL-15, and IL-21 were also implicated in inducing PD-1 on the surface of CD4 + and CD8 + T cells (58). Although these gc cytokines are considered proinflammatory, our findings involving Tim-3 upregulation, as well as those of others regarding PD-1, suggest that they are also responsible for the activation of inhibitory pathways.…”
Section: Discussionmentioning
confidence: 40%
“…These studies did not examine Tim-3 or PD-1 expression on T cells. The gc cytokines IL-2, IL-7, IL-15, and IL-21 were also implicated in inducing PD-1 on the surface of CD4 + and CD8 + T cells (58). Although these gc cytokines are considered proinflammatory, our findings involving Tim-3 upregulation, as well as those of others regarding PD-1, suggest that they are also responsible for the activation of inhibitory pathways.…”
Section: Discussionmentioning
confidence: 40%
“…Further analysis of the CD25 − population following influenza infection revealed that the expression of PD-1, another marker associated with TCR engagement, was upregulated but to a much lesser degree in this subset. It has been demonstrated that while PD-1 is indeed up-regulated markedly after TCR engagement, it can also be up-regulated in the presence of gamma-chain cytokines, although to a much lesser extent than following TCR engagement [46]. Subsequent analysis of PD-1 expression in the CD8 + CD25 + (TCR-triggered) and the CD8 + CD25…”
Section: Discussionmentioning
confidence: 99%
“…This apparent paradox may be explained by the fact that B7H1 is engaged in the immune exhaustion process. Concurrent thyroiditis may provide a microenvironment enriched with IFNg, IL10, IL6, and common g-chain cytokines that are able to increase B7H1 expression (Kinter et al 2008, Wölfle et al 2011, Taube et al 2012.…”
Section: Discussionmentioning
confidence: 99%